Commitment Level of Polytechnics Teachers and Strategies to Enhance it-A Study - Gupta, B. L.; Pande, H. S. (Journal of Engineering Education Transformations, 1999)
Technical education has been making significant contribution to India'sÂ economic development. Substantial diversi.fication and enhancement of produchon have been possible mainly because of the competent manpower devel oped by the technical institutions ofÂ the country.